IMPLEMENTATION OF CHARACTER EDUCATION IN INTEGRATED ISLAMIC KINDERGARTEN CITY OF PALEMBANG - Padli Padli; Nyayu Khadijah; Akmal Hawi (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2022)
This study aims to analyze character education in the Integrated Islamic Kindergarten in Palembang and the factors that influence the implementation of character education in the Integrated Islamic Kindergarten in Palembang. This type of research is qualitative research. The data collection technique used interview, observation, and documentation techniques. In contrast, the data analysis technique adopted an interactive pattern developed by Milles and Huberman: data reduction, data presentation, and conclusion drawing. The results of these findings are that the implementation of character education in the IT Kindergarten in Palembang City is by forming and educating children to become children with character, including parenting patterns (Hadanah), role models, and habituation. Then, the factors influencing the implementation of Character Education are the educational background of teachers, available budget, facilities, infrastructure, the government as a policy maker, and schools, in this case, kindergartens. Parents as the first shaper of the child's character, and the community or environment that reflects the application of culture and national character in everyday life. The success of character education will be triumphant when all elements carry out their respective functions properly.